Kinerja dari Prototipe Robot Visual Pengumpul Sampah Perairan dengan Remote Control menggunakan Telemetri - Sulistyawan, Faiz; Waluyanti, Sri (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
The making of prototype robot waste water collection aims to know the performance itself. The prototype of the Aquatic Waste Collection Robot is designed to float and clean trash in remote controlled waters. The main control drives a series of DC brushless motors to drive while the MG995 servo motor drives a rudder or defender. The device is also equipped with a camera as a medium to see the condition of the robot directly or in real time which will be displayed on the monitor screen. The camera and screen are connected to a telemetry circuit consisting of a transmitter and receiver with a frequency of 5.8 GHz, and a Li-Po battery as a source of robot power supply. The results of prototype testing of water garbage collection robots have been carried out in Embung Langensari Yogyakarta with a depth of 2-3 meters and an area of 5890 m2, the robot can go with a maximum speed of 0.3 m / s with or without the garbage load. Garbage nets used with a capacity of 20 liters. Robots can maneuver to turn right or left with a rudder. In the garbage collection process, this robot can collect relatively small waste